Morphological characterization of adolescents tennis players - Rica, Roberta Luksevicius; Miranda, João Marcelo de Queiros; Gomes, João Henrique; Barbosa, Welmo A.; Santana, Cleidison M.; Viana, Michel Vetoraci; Junior, Francisco Luciano Pontes; João, Gustavo Allegretti; Maia, Adriano Fortes; Bocalini, Danilo Sales (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The anthropometric profile investigation is considered an important parameter to success in sports, however, there is no available study that investigated biometrics parameters in national level teenage players. In this way the aim of this paper was evaluate the anthropometric characteristics of adolescent tennis players by national level. Methods: The anthropometric and body composition evaluation were recognized on 30 adolescents practicing tennis with at least four years. The following parameters were evaluated: body composition, skin folds, perimeter and fat member. Results: The adolescent tennis players presented eutrophication status according to the mean BMI (kg/m 2 ) and values ​​within normality in relation to the percentage of fat (%). Conclusion: The results of the present study resembled the findings of literature on the anthropometric characteristics of amateur and professional tennis players.